Outcome and Safety of Thulium Fiber Laser for Urinary Stone Diseases - a Cross-sectional Study - Thakur, Dipak Kumar; Ansari, Imran; Agrawal, Chandra Shekhar (Birat Journal of Health Sciences, 2023)
Introduction: Thulium fiber laser (TFL) was introduced into the urological armamentarium as an alternative to Ho:YAG as an energy source. This study aims to assess the outcome and safety of RIRS using TFL in patients with proximal ureteric and renal stone requiring intervention. Methods: It was a hospital based cross-sectional study conducted in the Department of Urology of of Birat Medical College- Teaching Hospital over a period of 6 months (September 2022 to February 2023) in adults patients with stone size upto 20mm. The outcome and safety of the procedure was assessed for stone clearance, operative time, hospital stay and procedure related complications. Results: We included initial 50 cases. Mean age, calculus size, calculus volume and calculus density were 40.02± 13.97 years, 14.45±3.36mm, 534.46±209.53 mm3, 1046.96±236.88 HU respectively. Complete stone clearance was achieved in 92% (46 cases) with 8% CSRF (4 cases). Procedure related complications occurred in 12% (8) cases. Conclusions: The TFL as a newer energy source is safe and effective for lithotripsy during RIRS with acceptable complications.